Three‐dimensional plotting of a cell‐laden alginate/methylcellulose blend: towards biofabrication of tissue engineering constructs with clinically relevant dimensions. (22nd July 2015) - Schütz, Kathleen; Placht, Anna‐Maria; Paul, Birgit; Brüggemeier, Sophie; Gelinsky, Michael; Lode, Anja
Abstract: Biofabrication of tissue engineering constructs with tailored architecture and organized cell placement using rapid prototyping technologies is a major research focus in the field of regenerative therapies. This study describes a novel alginate‐based material suitable for both cell embedding and fabrication of three‐dimensional (3D) structures with predefined geometry by 3D plotting. The favourable printing properties of the material were achieved by using a simple strategy: addition of methylcellulose (MC) to a 3% alginate solution resulted in a strongly enhanced viscosity, which enabled accurate and easy deposition without high technical efforts. After scaffold plotting, the alginate chains were crosslinked with Ca 2+ ; MC did not contribute to the gelation and was released from the scaffolds during the following cultivation. The resulting constructs are characterized by high elasticity and stability, as well as an enhanced microporosity caused by the transient presence of MC. The suitability of the alginate/MC blend for cell embedding was evaluated by direct incorporation of mesenchymal stem cells during scaffold fabrication. The embedded cells showed high viability after 3 weeks of cultivation, which was similar to those of cells within pure alginate scaffolds which served as control. Maintenance of the differentiation potential of embedded cells, as an important requirement for the generation of functional tissue engineering constructs, was proven for adipogenic differentiation as a model for soft tissue formation. In conclusion, the temporary integration of MC into a low‐concentrated alginate solution allowed the generation of scaffolds with dimensions in the range of centimetres without loss of the positive properties of low‐concentrated alginate hydrogels with regard to cell embedding. Copyright © 2015 John Wiley & Sons, Ltd.